Trees on Farms to Improve Livelihoods and the Environment - Somarriba, Eduardo (2021)
This publication shows how the advances of the joint work of FTA and the Trees on Farms for Biodiversity project in Nicaragua and Honduras were used to: 1) increase the visibility of trees on living fences of cattle ranches in the national information system of forest resources in Honduras, and in both national reporting systems and sector development programs for the livestock sector; and 2) develop science-based knowledge and tools needed to improve the design and management of trees in the shade canopy of agroforestry systems for cocoa and coffee. Increasing the visibility of trees on farms and incorporating them into public policy and development initiatives, require outstanding science-based knowledge to be generated, shared and thoroughly discussed with key personnel in public institutions and organizations of the private sector, including education and information systems.